Municipal policy of EU countries - Akhmerov, Oleksandr O.; Ахмеров, Олександр Олександрович; Ахмеров, О.О.; Ахмеров, Александр Александрович (Одеса: Фенікс, 2018)
In the article the essence of municipal policy is considered, its characteristic features are determined. The present state of practical realization of municipal policy in EU countries is analysed. The directions of reorganization in the system of local self-governance in Europe are identified, which include functional and procedural reformation; structural reform; financial reform; change in the number of administrative-territorial units. It has been clarified that in the last decade in the EU the reform of the system of local self-government was aimed at strengthening local levels of governance and consolidation of territorial communities. Other reforms have been identified. For example, French is aimed at developing a regional level of self-government. It has been established that the success of decentralization-related reforms in European countries largely depends on a pan European policy of allocating funds for development of regions. It has been proved that for the states that were in a transit state during the process of reforming the system of local self-government, the subsidy mechanism allowed the use of additional resources for the purpose of development of territorial communities, saving both national and municipal budgets for maintenance of current expenses.

В статті розглянуто сутність муніципальної політики, визначено її характерні особливості. Проаналізовано сучасний стан практичної реалізації муніципальної політики в країнах ЄС. Визначено напрями реорганізації в системі місцевого самоврядування у Європі, до яких віднесено функціонально-процесуальне реформування; структурне реформування; фінансове реформування; зміна кількості адміністративно-територіальних одиниць. З’ясовано, що за останнє десятиліття у країнах ЄС реформування системи місцевого самоврядування було спрямоване на посилення локальних рівнів управління та укрупнення територіальних громад. Визначено і інші моделі реформ. Так, наприклад, французька спрямована на розвиток регіонального рівня самоврядування. Встановлено, що успішність реформ пов’язаних з децентралізацією в європейських країнах багато в чому залежить від загальноєвропейської політики розподілу коштів призначених для розвитку регіонів. Доведено, що для держав, які знаходились в стані транзиту в процесі реформування системи місцевого самоврядування механізм субсидій дозволив використати додаткові ресурси з метою розвитку територіальних громад, заощаджуючи кошти як загальнонаціонального, так і муніципальних бюджетів для забезпечення поточних витрат.

В статье рассмотрены сущность муниципальной политики, определены ее характерные особенности. Проанализировано современное состояние практической реализации муниципальной политики в странах ЕС. Определены направления реорганизации в системе местного самоуправления в Европе, к которым отнесены функционально-процессуальное реформирования; структурное реформирование; финансовое реформирование; изменение количества административно-территориальных единиц. Выяснено, что за последнее десятилетие в странах ЕС реформирования системы местного самоуправления было направлено на усиление локальных уровней управления и укрупнение территориальных общин. Определены и другие модели реформ. Так, например, французская направлена ​​на развитие регионального уровня самоуправления. Установлено, что успешность реформ, связанных с децентрализацией в европейских странах, во многом зависит от общеевропейской политики распределения средств предназначенных для развития регионов. Доказано, что для государств, которые находились в состоянии транзита в процессе реформирования системы местного самоуправления механизм субсидий позволил использовать дополнительные ресурсы в целях развития территориальных общин, экономия средства как общенационального, так и муниципальных бюджетов для обеспечения текущих расходов.
Akhmerov О. О. Municipal policy of EU countries / О. О. Akhmerov // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), А. В. Полухіна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2018. – Вип. 61. – С. 174-183.
Keywords: municipal policy; local self-government; EU countries; local democracy; civil society; муніципальна політика; місцеве самоврядування; країни ЄС; локальна демократія; громадянське суспільство; муниципальная политика; местное самоуправление; страны ЕС; локальная демократия; гражданское общество; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law